FISHING ACTIVITY, SIZE DISTRIBUTION, TAG RELEASED AND RECAPTURE OF TUNA TAGGING IN EASTERN INDONESIAN WATERS - Moh. Natsir; Agustinus Anung Widodo; Budi Iskandar Prisantoso (Indonesian Fisheries Research Journal, 2012)
Tagging of tropical tunas has a long history in Indonesian waters. Since 1987 tuna tagging has been conducted in Indonesian Waters. Tuna tagging in 2008 in eastern Indonesian waters was conducted in collaborative program with SPC to obtain new data about biological aspect and stock assessment of tuna. This tuna tagging was successfully conducted at 86 locations, with a total of 25,197 tuna tagged with conventional tags, at an average of around 900 fish per fishing day. The releases of conventional tags comprised of 19,576 skipjack (77.7%), 5,267 yellowfin (20.9%) and 354 bigeye (1.4%). From the length frequency composition, the skipjack size range was wide, between 29 – 83 cm, but mostly between 35 and 40 cm with 38.9 cm average. The yellowfin size range of 28 – 65 cm, with most fish between 37 and 41 cm of 40.1 cm average. The small numbers of bigeye tagged were mostly larger than 38 cm, ranging from 29 to 58 cm with 41.3 cm average. During the taggingcruise, bait fish to support the fishing activity was relatively easily found in and around the survey area, either with direct catching using bouke ami net or purchasing from the lift net fisherman. By the end of 2010, 4,594 tags was recovered representing a relatively high recovery rate of 18.2% overall.